Tinjauan Kebijakan Lingkungan Hidup terhadap Standar Baku Pemilihan Lokasi Tempat Pembuangan Akhir Sampah - Lumongga, Retta Ida (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2014)
One of the environmental problem is related to the waste, and to the place where the waste is collected. There are standards that govern the procedures for the selection of landfill site. However, with the advent of new restrictions due to developments in environmental policy , it is necessary to conduct a review of the standards on the basis of policy development, at international level, national level and regional level . The method used is to follow the framework undertakes a review of the results of data collection in the form of various policy documents , standards , evaluation of the results of environmental studies and literature . The results: with the development of the environmental policy of the additional word ‘ protection ‘ to the new law has the potential to influence the standards and their application ; absence of authority over the abundance of local government so that the selection of the location of landfills need to understand the local waste management policies; development of understanding landfills than a landfill ( the standard) into a waste processing and direct open - dumping into the sanitary landfill;aesthetic standards of the processing can reduce landfill trash.